An maximum power point tracking interface circuit for low-voltage DC-type energy harvesting sources - Eun Jeong Yun; Jong Tae Park; Chong Gun Yu (Institute of Advanced Engineering and Science, 2022)
This paper presents a maximum power point tracking (MPPT) interface circuit for low-voltage DC-type energy harvesting sources such as light and thermal energy. Most energy harvesting systems used in miniature-sized sensor systems require start-up circuits because the output voltages of small-sized energy transducers are very low and not enough to directly power electronic systems. The proposed interface circuit is driven directly by the low output voltages of small size energy transducers, eliminating the need for complex start-up circuitry. A simple MPPT controller with the fractional open-circuit voltage (FOCV) method is designed and fabricated in a 65-nm complementary metal oxide semiconductor (CMOS) process. Measurement results show that the designed circuit can track the MPP voltage even in the presence of the open-circuit voltage fluctuations and can operate properly at operating voltages as low as 0.3 V. The interface circuit achieves a peak power efficiency of 97.1% and an MPPT accuracy of over 98.3%.